Vocational High School Graduate Wage Gap: The Role of Cognitive Skills and Firms - Joop Hartog; Pedro S. Raposo; Hugo Reis (Center for Economic Studies and ifo Institute (CESifo), 2018)
Comparing cohorts born between 1951 and 1994, we document and interpret changes in the wage differential among graduates from secondary education with a vocational and a general curriculum.. The wage gap initially increased and then decreased. We find that these changes cannot be attributed to simple compositional shifts in the economy, but instead relate to important changes in worker allocation to firms that are heterogeneous in wage policies: the demise of assortative matching between workers and firms that worked out favourably for vocational graduates.
Keywords: J31; I26; 330; returns to education; vocational wage gap